The Impact of Financial Literacy, Financial Behavior, and FinTech Adoption on Investment Decisions Among University Students - Anggraeni, Friska; Putra, Adrie (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Investigate the influence of financial literacy, financial behavior, and financial technology (FinTech) on investment decisions made by students in West Jakarta. The research employs a quantitative approach with a descriptive and causal-comparative research design to understand the relationships between these variables. Specific Background: Data were collected through a survey using a specially designed questionnaire distributed to students who met the inclusion criteria, namely those who are actively enrolled in university and have experience in investment activities, using purposive sampling techniques. A total of 100 students participated as respondents in this study. The data analysis method used is multiple linear regression, which allows the researchers to measure the simultaneous effects of financial literacy, financial behavior, and FinTech on investment decisions. Results: Financial literacy has a positive and significant influence on students' investment decisions. Moreover, financial behavior, which includes how individuals manage their personal finances, also plays a crucial role in influencing investment decisions. FinTech, encompassing digital applications and platforms for financial management and investment, was also found to have a significant impact on investment decisions. The combination of strong financial literacy, healthy financial behavior, and the effective utilization of FinTech has been proven to enhance the quality of investment decisions made by students. Implications: Highlight the importance of developing more targeted financial literacy programs and promoting the use of financial technology as an investment aid among students